The Contribution of Tourism Industry Cash Flows to Economic Growth “Middle East Evidence” - ALADWAN, Mohammad (Journal of Environmental Management and Tourism, 2023)
This study aims to verify the extent to which the tourism sector contributes to economic growth measured by gross domestic income (GDP) in emerging countries. This study relied on the applied research method through correlation, simple and multiple regression. The study sample consisted of all tourism companies in Jordan. Quarterly Cash flows of tourism sector was traced from 2008-2021 and linked to GDP. The study reached the following conclusions, the simple regression confirmed the positive impact for all economic sectors including tourism sector on GDP; on the other hand, the multiple regression results for the joint influence of all sectors together on GDP only five sectors including tourism found with positive impact on GDP. Further evidence was found for the importance of tourism contribution to local income after excluding this sector from total earnings, the explanatory power of all sectors to GDP was decreased by 25%. The overall results of study recommended to give more attention to this sector in emerging economics particularly middle east countries.